Pemberdayaan Ekonomi dan Lingkungan Kelompok Masyarakat Adat Tiyuh Tanjung Seneng, Kota Bandar Lampung - Trijoko Prasetyo; Titik Nur Aeny; Yunia Amelia (Jurnal Nusantara Mengabdi, 2021)
Purpose: The purpose of this community service activity is to increase the knowledge and understanding of the target partner community regarding entrepreneurship, business management, and good financial governance in responding to the current economic impact of the COVID-19 pandemic. In addition, it is aimed at giving insight into family economic income regarding cultivated plants that have high economic potential/value but they are able to maintain eco-friendly ecosystems and conservation to be developed around the house yard. Method: It is carried out through counseling, training, and mentoring for indigenous groups located at the traditional house of the partner location of the Tiyuh Tanjung Traditional Village. Result: This community service activity was planned through the stages of an activity planning meeting which was attended by all members. The next stage, each of them prepared material according to their respective fields. Then each of them made initial contact and communicated with the head of the traditional group to prepare for the implementation of the activity. Finally, it was agreed that the implementation of service activities at the Tiyuh Tanjung Seneng location involved the participants of the traditional group, activities which were held in the second week of August 2021. Conclusion: It can be concluded that there was an increase of knowledge and understanding in the use of yards for planting productive trees for training participants on average 35 percent of all participants.